Low-temperature impedance spectroscopic analyses of ceramic electrodes based on Mo and Co co-doped SnO2 - Ferreira, Diego H.O.; Vaz, Isabela C.F.; Rubinger, Rero M.; Buono, Camila; Rocha, Leandro S.R.; Ponce, Miguel A.; Longo, Elson; Simões, Alexandre Z. [UNESP]; Moura, Francisco (National Library of Serbia, 2019)
Low resistive electrodes based on Co and Mo co-doped SnO2 were prepared by the conventional solid-state reaction and sintered at 1250 °C for 2 h. Concentration of Co2O3 precursor was unchanged (1 mol%), while MoO3 was varied (0.25, 0.50 to 0.75 mol%) to promote conductivity. The structural and microstructural characterization revealed that the samples have a rutile-type structure without secondary phases and large rutile grains with low porosity. Electrical measurements on DC mode have shown a semiconductor behaviour of the SnO2 samples doped with 0.25 and 0.75 at. % of Mo at temperatures below 50 K, indicating their suitability for low-temperature electronic applications. Impedance measurements indicate reduced energy barriers of less than 1 meV formed between highly conductive crystallites for the SnO2 samples doped with 0.25 and 0.75 at. % of Mo. The sample with Mo content of 0.50 at. % presented a higher energy barrier at a few hundredths of eV, with space charges at the crystallite boundaries.
Keywords: Co/Mo co-doped SnO2; Complex impedance spectroscopy; Low-temperature electronic applications